Exploring gender, work and living conditions and health - suggestions for contextual and comprehensive approaches - Härenstam, Annika (Scandinavian Journal of Work, Environment & Health, 2009)
New methods are needed to complement traditional epidemiological methods in the analyses of complex multivariate exposures. Contextual and comprehensive analyses such as multilevel and cluster analyses are particularly suitable for comparisons of women’s and men’s risk factors for health in working life as well as for guidance in preventive action. Such methodologies are presented in this discussion paper. Contextual and comprehensive (or holistic) approaches help identify the gender-structured situations for women and men and facilitate the discovery of differences among all women and all men. Empirical studies using these approaches show that it is important to take gender composition in both the workplace and the sector into consideration when exploring risk factors for health.
Keywords: cluster analysis; comprehensive approach; contextual approach; discussion paper; epidemiology; gender; gender-based analysis; health; holistic approach; living conditions; multilevel analysis; occupational health; woman; work